Determination of Water Saturation Using Gas Phase Partitioning Tracers and Time‐Lapse Electrical Conductivity Measurements. Issue 2 (21st May 2013) - Johnson, T.C.; Oostrom, M.; Truex, M.J.; Thomle, J.N.; Wietsma, T.W.
Abstract : Water saturation is an important indicator of contaminant distribution and plays a governing role in contaminant transport within the vadose zone. Understanding the water saturation distribution is critical for both remediation and contaminant flux monitoring in unsaturated environments. In this work, we propose and demonstrate a method of remotely determining water saturation levels using gas phase partitioning tracers and time‐lapse bulk electrical conductivity measurements. The theoretical development includes the partitioning chemistry for the tracers we demonstrate (ammonia and carbon dioxide), as well as a review of the petrophysical relationship governing how these tracers influence bulk conductivity. We also investigate methods of utilizing secondary information provided by electrical conductivity breakthrough magnitudes induced by the tracers. We test the method on clean, well characterized, intermediate‐scale sand columns under controlled conditions. Results demonstrate the capability to accurately monitor gas breakthrough curves along the length of the column according to the corresponding electrical conductivity response, and to adequately determine partitioning coefficients, leading to accurate water saturation estimates. This work is motivated by the need to develop effective characterization and monitoring techniques for contaminated deep vadose zone environments, and provides a proof‐of‐concept toward uniquely characterizing and monitoring water saturation levels at the field scale and in three‐dimensions using electrical resistivity tomography.